Enriching the ant tree of life: enhanced UCE bait set for genome‐scale phylogenetics of ants and other Hymenoptera. Issue 6 (7th March 2017) - Branstetter, Michael G.; Longino, John T.; Ward, Philip S.; Faircloth, Brant C.
Summary: Targeted enrichment of conserved genomic regions (e.g. ultraconserved elements or UCEs) has emerged as a promising tool for inferring evolutionary history in many organismal groups. Because the UCE approach is still relatively new, much remains to be learned about how best to identify UCE loci and design baits to enrich them. We test an updated UCE identification and bait design workflow for the insect order Hymenoptera, with a particular focus on ants. The new strategy augments a previous bait design for Hymenoptera by (i) changing the parameters by which conserved genomic regions are identified and retained, and (ii) increasing the number of genomes used for locus identification and bait design. We perform in vitro validation of the approach in ants by synthesizing an ant‐specific bait set that targets UCE loci and a set of 'legacy' phylogenetic markers. Using this bait set, we generate new data for 84 taxa (16/17 ant subfamilies) and extract loci from an additional 17 genome‐enabled taxa. We then use these data to examine UCE capture success and phylogenetic performance across ants. We also test the workability of extracting legacy markers from enriched samples and combining the data with published datasets. The updated bait design (hym‐v2) contained a total of 2590‐targeted UCE loci for Hymenoptera, significantly increasing the number of loci relative to the original bait set (hym‐v1; 1510 loci). Across 38 genome‐enabled Hymenoptera and 84 enriched samples, experiments demonstrated a high and unbiased capture success rate, with the mean locus enrichment rate being 2214 loci per sample. Phylogenomic analyses of ants produced a robust tree that included strong support for previously uncertain relationships. Complementing the UCE results, we successfully enriched legacy markers, combined the data with published Sanger datasets and generated a comprehensive ant phylogeny containing 1060 terminals. Overall, the new UCE bait design strategy resulted in an enhanced bait set for genome‐scale phylogenetics in ants and other Hymenoptera. Our in vitro tests demonstrate the utility of the updated design workflow, providing evidence that this approach could be applied to any organismal group with available genomic information.